IMPLEMENTATION MODEL INTERNET OF THINGS ON MICRO MEDIUM ENTERPRISE IN BEKASI REGIONAL - Hamzah Muhammad Mardi Putra; Arief Teguh Nugroho (Bajang Institute, 2022)
The purpose of this study is to identify the use of technology and analyze the influence of technology and the internet on the use of social media on Micro, Small and Medium Enterprises in the District Bekasi. The target to be achieved is to identify the use of technology and the internet on MSME actors and analyzethe influence of technology use on the use of social media on MSME actors. The Framework of Thought in this study proposes the development of the Technology Readiness Index (TRI) model consisting of Optimism, Innovativeness, Discomfort, as well as the Insecurity and Technology Acceptance Model (TAM) consisting of the proposed Perceived Ease of Use and Perceived Usefulness by Davis (1989) then combined by Putra (2017) and Rahman (2017) which influenced the use of Social Media by Micro, Small and Medium Enterprises (MSMEs) in Bekasi Regency. The respondents in this study consisted of micro, small and medium enterprises in Bekasi Regency who used Social Media in their businesses. The results of this study indicate that the respondent's monthly expenditure in the Jababeka Industrial Estate is more than 5 million with 40.3%. Respondents were grouped into expenditures under 1 million, 1-3 million, 3-5 million and more than 5 million.